Menakar Keadilan dalam Pemutusan Hubungan Kerja Sepihak: Perlindungan Hukum Bagi Buruh dalam Perspektif Undang-Undang Cipta Kerja - Ahlan Sihabillah; Deny Guntara; Muhamad Abas (CV Rewang Rencang, 2025)
In everyday life, economic activities often involve legal agreements between parties regarding an agreed-upon object. In Indonesia's Civil Law system, various types of contracts are regulated, including employment relationships. This study aims to identify the factors leading to termination of employment (PHK) based on the Job Creation Law and to explore legal protection for workers who experience unilateral termination. The focus of this research includes the analysis of employment termination mechanisms under the Job Creation Law, and the legal efforts available to workers against unilateral termination carried out by companies. This research is normative in nature, employing a qualitative method and a normative juridical approach. This approach involves examining rules, norms, and regulations relevant to unilateral termination through a literature study, which includes reading, quoting, copying, and analyzing related theories. The primary data used are secondary data, while primary data serve as supporting data. The findings indicate that there are cases of unilateral termination that violate the Job Creation Law. The ambiguity of sanctions in the law creates loopholes for companies to carry out unilateral terminations. Workers affected by unilateral termination are entitled to legal protection as stipulated in the Job Creation Law, which is part of the commitment to improving economic quality. Companies that conduct unilateral termination must also face sanctions in accordance with violations of the law and the uncertainty of citizens' constitutional rights.